Contemporary Canadian federalism : foundations, traditions, institutions - Gagnon, Alain (University of Toronto Press, 2009)
Filled with stimulating work that bridges the gap between distinctive traditions in English- and French-Canadian scholarship on federalism, this important volume is required reading for understanding provincial-federal relations and Canadian governance.